The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4174/astr.2020.99.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and oncologic outcomes in patients with preoperative clinical T3 and T4 colon cancer who were staged as pathologic T3

Abstract: Purpose: Clinically suspected T4 stage colon cancer from a preoperative exam is often diagnosed as T3 stage colon cancer pathologically after surgery, raising concerns about understaging. The aims of this study were to compare the survival of clinical T3 and T4 colon cancer patients who had received a pathologic T3 stage diagnosis postoperatively. Methods: Patients who were diagnosed with pathologic T3 stage colon cancer postoperatively were reviewed. Patients with clinically suspected T3 or T4 stage cancer on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…56 Some authors report a worse prognosis for patients who had suspected cT4 before surgery but had been diagnosed with pT3, because they were more likely to have perforation. 57 Moreover, in a previous report (COLOPEC trial) the authors showed a 3% (experimental group) and a 4% (control group) of patients with histologically pT2-pT3 and preoperative cT4. In our results, we will expect a similar rate of preoperative failure of pT4.…”
Section: Discussionmentioning
confidence: 90%
“…56 Some authors report a worse prognosis for patients who had suspected cT4 before surgery but had been diagnosed with pT3, because they were more likely to have perforation. 57 Moreover, in a previous report (COLOPEC trial) the authors showed a 3% (experimental group) and a 4% (control group) of patients with histologically pT2-pT3 and preoperative cT4. In our results, we will expect a similar rate of preoperative failure of pT4.…”
Section: Discussionmentioning
confidence: 90%
“…Перфорация опухоли кишечника происходит в результате ишемии и некроза кишечной стенки [9]. Частота перфорации кишечника у пациентов с КРР варьирует от 1,2 до 10,0 % [10][11][12].…”
Section: Introductionunclassified